2007 Asia and South Pacific Design Automation Conference 2007
DOI: 10.1109/aspdac.2007.358111
|View full text |Cite
|
Sign up to set email alerts
|

Fixing Design Errors with Counterexamples and Resynthesis

Abstract: Abstract-In this work we propose a resynthesis framework, called CoRé, that automatically corrects errors in digital designs. The framework is based on a simulation-based abstraction technique and performs error correction through two innovative circuit resynthesis solutions: Distinguishing-Power Search (DPS) and Goal-Directed Search (GDS), which modify the functionality of a circuit's internal nodes to match the correct behavior. In addition, we propose a compact encoding of resynthesis information, called Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 9 publications
0
39
0
Order By: Relevance
“…Pairs of bits to be distinguished: In [7], it was observed that a set of input signatures S1, ...Sx can implement a target signature S f , if and only if, every pair of different bits in S f is distinguished by at least one Sx. Example 1.…”
Section: Determining Logical Feasibility With Signaturesmentioning
confidence: 99%
See 1 more Smart Citation
“…Pairs of bits to be distinguished: In [7], it was observed that a set of input signatures S1, ...Sx can implement a target signature S f , if and only if, every pair of different bits in S f is distinguished by at least one Sx. Example 1.…”
Section: Determining Logical Feasibility With Signaturesmentioning
confidence: 99%
“…The next step enables efficient search for logic transformations. Through logic simulation, we partially characterize the behavior of each node in the subcircuit with a signature [8,7,25]. We then use these signatures to efficiently determine whether a logic transformation generating the desired topology is possible.…”
Section: Introductionmentioning
confidence: 99%
“…The aim of automated debugging is the highlighting of potential fault locations to an engineer to reduce the complexity for a subsequent manual debugging session. Thus, fixing the faulty behavior remains a manual task to avoid unexpected changes that may be introduced by methods that perform repairs automatically [4].…”
Section: Introductionmentioning
confidence: 99%
“…Based on circuit similarity, the placement and routing of the modified netlist can be derived from the layout of the original netlist obtained in the previous iteration. Unlike many existing algorithms for incremental designs [12,1], which require radical changes to existing computer-aided design (CAD) tools, we have developed a plugin that preserves the "push-button" feature in the commercial FPGA CAD tools.…”
Section: Introductionmentioning
confidence: 99%
“…Each of these steps requires a time-consuming resynthesis of the FPGA design. Incremental design methodology has been devised to save the recompilation time by maintaining the essential properties across consecutive iterations [9,12,23,1,25].…”
Section: Introductionmentioning
confidence: 99%